CSF cytokine profile in MOG-IgG+ neurological disease is similar to AQP4-IgG+ NMOSD but distinct from MS: a cross-sectional study and potential therapeutic implications. Issue 9 (6th June 2018) - Kaneko, Kimihiko; Sato, Douglas Kazutoshi; Nakashima, Ichiro; Ogawa, Ryo; Akaishi, Tetsuya; Takai, Yoshiki; Nishiyama, Shuhei; Takahashi, Toshiyuki; Misu, Tatsuro; Kuroda, Hiroshi; Tanaka, Satoru; Nomura, Kyoichi; et al.
Abstract : Objective: To evaluate cerebrospinal fluid (CSF) cytokine profiles in myelin oligodendrocyte glycoprotein IgG-positive (MOG-IgG+) disease in adult and paediatric patients. Methods: In this cross-sectional study, we measured 27 cytokines in the CSF of MOG-IgG+ disease in acute phase before treatment (n=29). The data were directly compared with those in aquaporin-4 antibody-positive (AQP4-IgG+) neuromyelitis optica spectrum disorder (NMOSD) (n=20), multiple sclerosis (MS) (n=20) and non-inflammatory controls (n=14). Results: In MOG-IgG+ disease, there was no female preponderance and the ages were younger (mean 18 years, range 3–68; 15 were below 18 years) relative to AQP4-IgG+ NMOSD (41, 15–77) and MS (34, 17–48). CSF cell counts were higher and oligoclonal IgG bands were mostly negative in MOG-IgG+ disease and AQP4-IgG+ NMOSD compared with MS. MOG-IgG+ disease had significantly elevated levels of interleukin (IL)-6, IL-8, granulocyte-colony stimulating factor and granulocyte macrophage-colony stimulating factor, interferon-γ, IL-10, IL-1 receptor antagonist, monocyte chemotactic protein-1 and macrophage inflammatory protein-1α as compared with MS. No cytokine in MOG-IgG+ disease was significantly different from AQP4-IgG+ NMOSD. Moreover many elevated cytokines were correlated with each other in MOG-IgG+ disease and AQP4-IgG+ NMOSD but not in MS. No difference in the data was seen between adult and paediatric MOG-IgG+ cases. Conclusions: The CSF cytokine profile in the acute phase of MOG-IgG+ disease is characterised by coordinated upregulation of T helper 17 (Th17) and other cytokines including some Th1-related and regulatory T cells-related ones in adults and children, which is similar to AQP4-IgG+ NMOSD but clearly different from MS. The results suggest that as with AQP4-IgG+ NMOSD, some disease-modifying drugs for MS may be ineffective in MOG-IgG+ disease while they may provide potential therapeutic targets.